Assessing Public Reaction to Artificial Intelligence in Promoting Green Tourism and Infrastructure Initiatives in Indonesia's New Capital Nusantara - Fahlevi, Mochammad; Romli, Zainur; Asetya, Dimvy Rusefani; Dandi, Mochamad (Diponegoro University, 2025)
This study aims to answer these questions by examining the effectiveness of green tourism marketing strategies by the Indonesian government, utilizing social media platforms Instagram and X (formerly Twitter), and learning how the public perceives its initiative. We collected comments on government posts promoting green infrastructure and tourism and analyzed them using a mixed-method approach. Sentiments were divided into three categories: positive, neutral, and negative, using Natural Language Processing (NLP) techniques. The results reveal a general negative reception of AI-authored advertising messages, amounting to 64.18% disapproving comments for Instagram and 81.93% for X, both expressing suspicion toward the overuse of AI and lack of authenticity calling into question transparency as well as genuine intentions behind sustainability goals. While a few responders gave positive reviews, the fact that so many responses were bordering or fully negative indicates that there needs to be clearer and more genuine communication strategies. Our research helps illuminate how the public perceives aspects of green tourism marketing, thus underscoring the significance of authenticity in promotional practices designed for sustainable development.